Immuno-inflammatory mechanisms in cardio-oncology: new hopes for immunotargeted therapies - Miao, Meiqi; Liu, Xinxin; Zhang, Han; Dai, Hailong (Frontiers in Oncology, 2025)
Cardio-oncology is an emerging interdisciplinary field concerned with cancer treatment-related cardiovascular toxicities (CTR-CVT) and concomitant cardiovascular diseases (CVD) in patients with cancer. Inflammation and immune system dysregulation are common features of tumors and cardiovascular disease (CVD). In addition to the mutual exacerbating effect through inflammation, tumor treatments, including immunotherapy, chemotherapy, radiation therapy, and targeted therapy, may induce immune inflammatory reactions leading to cardiovascular damage. Cancer immunotherapy is currently a new method of cancer treatment. Immunotherapeutic agents, such as immune checkpoint inhibitors (ICIs), chimeric antigen receptor T cell immunotherapy (CAR-T), mRNA vaccines, etc., can induce anti-tumor effects by enhancing the host immune response to eliminate tumor cells. They have achieved remarkable therapeutic efficacy in clinical settings but lead to many immune-related adverse events (irAEs), especially CTR-CVT. Establishing specific evaluation, diagnostic, and monitoring criteria (e.g., inflammatory biomarkers) for both immunotherapy and anti-inflammatory therapy-related cardiovascular toxicity is vital to guide clinical practice. This article explores the role of immune response and inflammation in tumor cardiology, unravels the underlying mechanisms, and provides improved methods for monitoring and treating in CTR-CVT in the field of cardio-oncology.